Fitness evaluation tests for competitive sports - Nande, Prajakta J. (Himalaya Pub. House, 2010)
PART I : INTRODUCTION TO PHYSICAL FITNESS PART II : PERFORMANCE EVALUATION PART III : PERFORMANCE EVALUATION TESTS Part IV Body Composition Assessment Part V Prediction of Body Density, Body Fat and Lean Body Mass Based on Skinfolds, Body Mass and Circumferences Part VI Other Methods for Estimation of Body Fat Content Appendices Appendix I Appendix II Appendix III Appendix IV Appendix V Appendix VI Appendix VII Appendix VIII References.